2007
DOI: 10.1116/1.2794325
|View full text |Cite
|
Sign up to set email alerts
|

Photolithographic synthesis of high-density DNA probe arrays: Challenges and opportunities

Abstract: The continual need for increased manufacturing capacity in the production of GeneChip™ DNA probe arrays, and the expanding use of these arrays into new areas of application such as molecular medicine, has stimulated the development of new chemistries and production methods with higher efficiency and resolution. For current production methods based on contact photolithography, modifications in substrate materials and photoactivated synthesis reagents have provided significant improvements in array performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Although this strategy did not improve the activity of cluster II or cluster III RIPtides, a significant increase in potency was observed for clusters IV and V RIPtides. Interestingly, we found that several sequenceextended versions of cluster IV RIPtides showed nanomolar IC 50 values in TRAP assays (supplemental Table 1, entries [35][36][37][38][39][40]. These observations are consistent with previous observations that longer DNA oligonucleotides targeting an overlapping region in hTR exhibit inhibitory activity against telomerase in vitro (45).…”
Section: -Ome Riptide Microarrays and Telomerase Inhibitionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although this strategy did not improve the activity of cluster II or cluster III RIPtides, a significant increase in potency was observed for clusters IV and V RIPtides. Interestingly, we found that several sequenceextended versions of cluster IV RIPtides showed nanomolar IC 50 values in TRAP assays (supplemental Table 1, entries [35][36][37][38][39][40]. These observations are consistent with previous observations that longer DNA oligonucleotides targeting an overlapping region in hTR exhibit inhibitory activity against telomerase in vitro (45).…”
Section: -Ome Riptide Microarrays and Telomerase Inhibitionsupporting
confidence: 81%
“…Microarray Manufacture-For the fabrication of 2Ј-OMe oligonucleotide-based high density microarrays, a photoresist technique based in I-line (365 nm) projection lithography was utilized (35). This method (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether their function is to diagnose disease, detect specific DNA sequences, screen for bioterrorism agents, or identify specific cancer variants, biochips of all types are ushering in a new era of medical and biological research. Several different biochip variations are now commercially available [2][3][4][5] and have been used in clinical and research settings. These biochips exploit a complimentary relationship between a probe and labeled target to produce a sensing response upon interaction of the probe/target pair.…”
Section: Introductionmentioning
confidence: 99%
“…Today, stepper-based lithography in combination with solid-phase photoacid generating polymer films has demonstrated submicron DNA patterns. 19 Other examples of increasing the resolution of photolithographic DNA chips have been accomplished by including reduction optics in maskless projection lithography systems. However, these results are limited to CDs greater than 2 m. 20,21 For the in situ synthesis of nanoscale DNA patterns, photomask engineering or developing higher magnification projection optics would be impractical.…”
Section: Introductionmentioning
confidence: 99%